Experiment of Natural Cooling system Using Well Water - JUDE, EDMAN; noranai, zamri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The advent of technology would make human life more convenient, easier, and meaningful. Lots of new inventions and solutions are developed with the combination of technologies in several fields. Natural cooling system related systems are undergoing major development periodically as it becomes a big part of our life. A building with a large number of occupants requires many facilities. Furthermore, a cooling system is an important system for a building while cooling system that have been use nowadays requires more energy consumption and pollution. Thus, this can be controlled by using a natural cooling system using well water. Meanwhile, the idea of this cooling system is to install a well nearby the building and use the well water to cool down a building using a simple mechanical system. Most importantly, the cooling system is illustrated using a conceptual design house.